Sedentary Lifestyle dengan Risiko DM Tipe 2 pada Remaja di SMPN 27 Banjarmasin - Dhea Manto, Onieqie Ayu; Amaliah, Meina; Fayuning Tjomiadi, Cynthia Eka (Pustaka Galeri Mandiri, 2025)
Diabetes Mellitus Type 2 is a metabolic disease characterized by an increase in blood glucose levels and can cause serious complications. In teenagers, one of the main triggering factors is a sedentary lifestyle, which is the habit of moving less and sitting more for a long time, such as playing gadgets, watching television, or using a computer. This condition lowers energy burning, increases fat accumulation, and triggers insulin resistance which plays a role in the occurrence of Diabetes Mellitus Type 2. This research aims to identify sedentary lifestyle with the risk of DM Type 2 in teenagers at SMPN 27 Banjarmasin. The research design uses quantitative descriptive with a cross-sectional approach, involving 44 selected respondents through purposive sampling. The instruments used are Adolescent Sedentary Activity Questionnaire and Finnish Diabetes Risk Score. The results of this study are that the majority of teenagers at SMPN 27 Banjarmasin have a high sedentary lifestyle (84.1%) and a moderate risk of DM Type 2 (72,7%), especially at the age of 15, with the main trigger factors of inactive lifestyle, excessive gadget use, unhealthy diet, and family history, so early prevention is required